A Survey on Publish-Subscribe Internet Routing Paradigm - Zeeshan Ahmad; Zain ul Abidin Jaffri; Iftikhar Ali (Institute of Advanced Engineering and Science, 2013)
Current internet is incompetent and inept for the current trends of communication. The architecture of current internet was drafted almost 40 years ago and it is unable to cop up the problems aroused in context of security, mobility, robustness, congested traffic and vice versa of this millennium. In this paper, publish–subscribe internet routing paradigm (PSIRP) a reengineered architecture of internet is comprehensively studied, which will resolve many of the problems faced by the internet today. Keeping in view the importance of information/data, the reengineered architecture of PSIRP proffers the information–centric communication instead of host–centric communication, in response to which many of the problems of current internet will be resolved automatically. As major portion of internet is publish/subscribe in nature so PSIRP can provide a flexible, efficient and powerful architecture for future internet network design.DOI: http://dx.doi.org/10.11591/ij-ict.v2i3.3562